A comparison of microscopic ink characteristics of 35 commercially available surgical margin inks. Issue 8 (1st October 2013) - Milovancev, Milan; Löhr, Christiane V.; Bildfell, Robert J.; Gelberg, Howard B.; Heidel, Jerry R.; Valentine, Beth A.
Abstract: Objective: To compare microscopic characteristics of commercially available surgical margin inks used for surgical pathology specimens. Study Design: Prospective in vitro study. Sample Population: Thirty‐five different surgical margin inks (black, blue, green, orange, red, violet, and yellow from 5 different manufacturers). Methods: Inks were applied to uniform, single‐source, canine cadaveric full‐thickness ventral abdominal tissue blocks. Tissue blocks and ink manufacturers were randomly paired and each color was applied to a length of the cut tissue margin. After drying, tissues were fixed in formalin, and 3 radial slices were obtained from each color section and processed for routine histologic evaluation, yielding 105 randomly numbered slides with each manufacturer's color represented in triplicate. Slides were evaluated by 5 blinded, board‐certified veterinary anatomic pathologists using a standardized scoring scheme. Statistical analyses were performed to evaluate for ink manufacturer effects on scores, correlation among different subjective variables, and pathologist agreement. Results: Black and blue had the most consistently high scores whereas red and violet had the most consistently low overall scores, across all manufacturers. All colors tested, except yellow, had statistically significant differences in overall scores among individual manufacturers. Overall score was significantly correlated to all other subjective microscopic scores evaluated. The average Spearman correlation coefficient among the 10 pairwise pathologists overall ink scores was 0.60. Conclusions: There are statistically significant differences in microscopic ink characteristics among manufacturers, with a notable degree of inter‐pathologist agreement.